25 TAHUN RISET PERPAJAKAN DI INDONESIA : ANALISIS CO-OCCURANCE - Al Rasyid, Rafi'i Habib; Batary Indradini, Shiva Kartika; Faridtaqy, Muhammad (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2024)
Research in the field of taxation is developing dynamically with a variety of discussion topics. However, it is necessary to map what has been achieved and identify future research directions. This study aims to explore the dynamics of tax research in Indonesia through publication related matric and co-occurance analysis techniques. This study analyzes 2470 keywords originating from 632 tax literature collected from 100 economic journals accredited by Sinta 1 and Sinta 2. The analysis results reveal that topics of tax research in Indonesia revolve around tax avoidance, tax compliance, tax aggressiveness and tax evasion. This study also identifies research constituents and important research topics that require further exploration from researchers in the future it is tax morale, tax complexity, trust issues, carbon tax and issues related to sustainability.